2009
DOI: 10.1007/s00405-009-1120-7
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi–Fujimoto and Kimura diseases: the selected, rare causes of neck lymphadenopathy

Abstract: Kikuchi-Fujimoto disease (KFD), also known as histiocytic necrotizing lymphadenitis, is a benign and self-limiting disease typically characterized by the enlargement of regional lymph nodes and accompanied by fever. KFD affects predominantly young adult females of Asian origin and is rarely seen in European countries, where it may cause diagnostic difficulties. Kimura disease is a rare and benign chronic inflammatory soft tissue disorder of unknown origin, characterized by a triad of painless subcutaneous mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
0
25
1
Order By: Relevance
“…Some evidence has indicated that the interaction between T H 1 and T H 2 lymhocytes may result in the excessive production of eosinophilotrophic cytokines, such as interleukin 4. Persistent antigenic stimulation from insect bites, parasitic infestation, candidal infection, or viral infection may cause the activation of this cytokine pathway, but further investigation is needed [3,4]. Kimura's disease involves the skin, lymph nodes, and salivary glands and is reported to be associated with nephrotic syndrome in approximately 15-19% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence has indicated that the interaction between T H 1 and T H 2 lymhocytes may result in the excessive production of eosinophilotrophic cytokines, such as interleukin 4. Persistent antigenic stimulation from insect bites, parasitic infestation, candidal infection, or viral infection may cause the activation of this cytokine pathway, but further investigation is needed [3,4]. Kimura's disease involves the skin, lymph nodes, and salivary glands and is reported to be associated with nephrotic syndrome in approximately 15-19% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular in iltrates consist of CD68+/CD123+ plasmacytoid histiocytes and transformed lymphocytes, mainly CD8+ T-lymphocytes expressing perforin involved in provoking apoptosis in target cells. Tubuloreticular structures in histiocytes, activated T cells and endothelial cells resemble those seen in SLE and viral disease [5]. However in SLE lymphadenitis neutrophils, plasma cells and haematoxylin bodies are often present [2].…”
Section: Introductionmentioning
confidence: 96%
“…The unspeci ic symptoms and the rarity of the illness means that there are many other differential diagnoses to consider, e.g. lymphoma, tuberculosis, metastatic disease, infectious mononucleosis, systemic lupus erythematous (SLE) or cat scratch disease [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations